PERSEPSI TENAGA PENDIDIK DAN TENAGA KEPENDIDIKAN TERHADAP PROGRAM BELAJAR DARI RUMAH - Barkat Amiruddin (Asosiasi Dosen Perguruan Tinggi Islam, 2020)
Abstract: Learning from Home Program have started since the covid19 pandemic entered Indonesia. Educators and education staff have implemented this program in schools. The purpose of this study was to determine the perceptions of teaching staff and education staff towards Learning from Home Program, the positive and negative impacts of the Learning from Home Program, and the obstacles in implementing the Learning from Home Program. The research method used is descriptive research with a qualitative approach. This research was conducted in 4 schools in the Central Bengkulu area, with 72 respondents. The results of the study found that most of the teaching staff and education staff did not like the Learning from Home Program, which was 61.1% or as many as 44 people. Positive impacts of the Home Learning Program, namely: (a) Learning becomes more time-efficient; (b) Train students to be more independent and responsible; (c) Making teachers more creative in making learning media and quizzes and multimedia supporting the learning process; and others. The negative impacts of the Home Learning Program, namely: (a) Reduced communication between teacher and students; (b) Learning becomes more difficult to control; (c) Difficulties in evaluating children; and others. Constraints in the implementation of the Learning from Home Program, namely: (a) Not all students have the tools to support the learning process; (b) Poor internet network in remote areas; (c) Lack of interaction and communication between students and teachers; and (d) There are still students who underestimate online learning. Keywords: Perception, Educators, Educators, Learning from Home Program Abstrak: Program belajar dari rumah sudah mulai dilakukan sejak pandemi covid19 masuk ke Indonesia. Tenaga pendidik dan tenaga kependidikan telah menerapkan program ini disekolah. Tujuan penelitian untuk mengetahui persepsi tenaga pendidik dan tenaga kependidikan terhadap program belajar dari rumah, dampak positif dan negatif Program Belajar dari Rumah, serta kendala dalam penerapan Program Belajar dari Rumah. Metode penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif. Penelitian ini dilakukan di 4 sekolah di daerah Bengkulu Tengah, dengan jumlah responden sebanyak 72 orang. Hasil penelitian ditemukan bahwa sebagian besar Tenaga pendidik dan tenaga kependidikan tidak menyukai Program belajar dari Rumah, yaitu sebanyak 61,1% atau sebanyak 44 orang. Dampak positif Program Belajar dari Rumah, yaitu: (a) Pembelajaran menjadi lebih hemat waktu; (b) Melatih siswa lebih mandiri dan bertanggung jawab; (c) Membuat guru lebih kreatif dalam membuat media pembelajaran dan kuis serta multimedia pendukung proses pembelajaran; dan lain-lain. Dampak negatif Program Belajar dari Rumah, yaitu: (a) Komunikasi yang berkurang antara guru dan siswa; (b) Pembelajaran jadi lebih susah untuk di control; (c) Kesulitan dalam evaluasi terhadap anak; dan lain-lain. Kendala dalam penerapan Program Belajar dari Rumah, yaitu: (a) Tidak semua siswa mempunyai alat pendukung proses pembelajaran; (b) Buruknya jaringan internet di daerah pedalaman; (c) Kurangnya interaksi dan komunikasi antara siswa dan guru; dan (d) Masih ada siswa yang menganggap remeh terhadap pembelajaran daring. Kata Kunci: Persepsi, Tenaga Pendidik, Tenaga Kependidikan, Program Belajar dari Rumah